Natural Exposure- and Vaccination-Induced Profiles of Ex Vivo Whole Blood Cytokine Responses to Coxiella burnetii - Raju Paul, Susan; Scholzen, Anja; Mukhtar, Ghazel; Wilkinson, Stephanie; Hobson, Peter; Dzeng, Richard K.; Evans, Jennifer; Robson, Jennifer; Cobbold, Rowland; Graves, Stephen; Poznansky, Mark C.; Garritsen, Anja; et al. (Frontiers in Immunology, 2022)
Q fever is a zoonotic disease caused by the highly infectious Gram-negative coccobacillus, Coxiella burnetii (C. burnetii). The Q fever vaccine Q-VAX is characterised by high reactogenicity, requiring individuals to be pre-screened for prior exposure before vaccination. To date it remains unclear whether vaccine side effects in pre-exposed individuals are associated with pre-existing adaptive immune responses to C. burnetii or are also a function of innate responses to Q-VAX. In the current study, we measured innate and adaptive cytokine responses to C. burnetii and compared these among individuals with different pre-exposure status. Three groups were included: n=98 Dutch blood bank donors with unknown exposure status, n=95 Dutch village inhabitants with known natural exposure status to C. burnetii during the Dutch Q fever outbreak of 2007-2010, and n=96 Australian students receiving Q-VAX vaccination in 2021. Whole blood cytokine responses following ex-vivo stimulation with heat-killed C. burnetii were assessed for IFNγ, IL-2, IL-6, IL-10, TNFα, IL-1β, IP-10, MIP-1α and IL-8. Serological data were collected for all three cohorts, as well as data on skin test and self-reported vaccine side effects and clinical symptoms during past infection. IFNγ, IP-10 and IL-2 responses were strongly elevated in individuals with prior C. burnetii antigen exposure, whether through infection or vaccination, while IL-1, IL-6 and TNF responses were slightly increased in naturally exposed individuals only. High dimensional analysis of the cytokine data identified four clusters of individuals with distinct cytokine response signatures. The cluster with the highest levels of adaptive cytokines and antibodies comprised solely individuals with prior exposure to C. burnetii, while another cluster was characterized by high innate cytokine production and an absence of C. burnetii-induced IP-10 production paired with high baseline IP-10 levels. Prior exposure status was partially associated with these signatures, but could not be clearly assigned to a single cytokine response signature. Overall, Q-VAX vaccination and natural C. burnetii infection were associated with comparable cytokine response signatures, largely driven by adaptive cytokine responses. Neither individual innate and adaptive cytokine responses nor response signatures were associated retrospectively with clinical symptoms during infection or prospectively with side effects post-vaccination.